NARCISSISTIC MOTHERHOOD AND THE DEVELOPMENT OF THE SELF IN CHILDREN - Amadeusz Furmanek; Martyna Susek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Maternal narcissism has been increasingly recognized as a significant factor influencing the psychological development of children. Early exposure to narcissistic parenting may disrupt attachment processes, emotional regulation, and the formation of a coherent sense of self. Children may face inconsistent caregiving, emotional invalidation, and conditional acceptance, which create a challenging developmental environment. Methods: This narrative review synthesizes current empirical and theoretical research examining the effects of narcissistic maternal behaviors on child development. Key mechanisms were analyzed, including insecure attachment, development of a “false self,” parentification, and intergenerational transmission of maladaptive patterns. Results: Children raised in environments characterized by maternal narcissism are more likely to develop insecure attachment styles, heightened reliance on external validation, and difficulties in regulating emotions. Adaptive strategies such as the formation of a “false self” may allow short-term coping but often limit authentic self-expression and long-term psychological well-being. Parentification adds additional emotional burden, as children assume caregiving roles prematurely, affecting autonomy and identity formation. Evidence also indicates that maladaptive relational patterns may be transmitted across generations, perpetuating vulnerabilities in self-concept and interpersonal functioning. Conclusions: Maternal narcissistic traits exert multifaceted and lasting effects on the development of identity, emotional regulation, and relational competence. Early relational experiences play a central role in shaping these outcomes, highlighting the importance of interventions that promote autonomy, emotional resilience, and a coherent sense of self. Future longitudinal research is needed to clarify developmental trajectories and identify protective factors that mitigate the impact of narcissistic parenting.